Outcomes of prevention of HIV mother-to-child transmission in Cipto Mangunkusumo Hospital - Dina Muktiarti; Nia Kurniati; Arwin Akib; Zakiudin Munasir (Paediatrica Indonesiana, 2012)
Background Human immunodeficiency virus (HIV) infectionis increasing worldwide. One foute of HIV transmission is frommother to child, during pregnancy, delivery or breastfeeding.Prevention of motherô€‚toô€‚child transmission may be an effectivestrategy to reduce the cases of new HIV infections.Objectives To investigate the incidence of HIV infection ininfants born to mothers with HIV and who received prophylactictherapy at birth, as well as to note the outcomes of HIVinfectedchildren in this program.Methods This retrospective study was carried out over a 9ô€‚yearperiod, from January 20 03 to December 2011. The participantswere HIVexposed infants who attended the HIV clinic, at theDepartment of Child Health, Cipto Mangunkusumo Hospital,Jakarta. Infants were treated according to the prevention ofmotherô€‚toô€‚child transmission (PMTCT) protocol at CMH.Parents' and infants' data was recorded. The end point of thisstudy was recording of HIVinfection status in the infants.Results There were 238 infants included in this study. HIVinfection was confirmed in 6 (2.5%) infants, while 170 (71.4%)subjects were uninfected, and 62 (26.1%) subjects were lostto followô€‚up. No subjects who underwent complete PMTCTmanagement were infected. Most subjects were male, fullô€‚tenn,and delivered by caesarean section in our hospital. The mostfrequently observed parental risk factor was intravenous druguse. Maternal antiretroviral therapy (ART) was given duringpregnancy in most cases. Morbidities in all subjects were low.Conclusion The PMTCT program at CMH was effective forreducing the number ofHIVinfected infants from mothers withHIY. [Paediatrlndanes. 2012;52:294-9].Â